Sisvaznat: Natural Flows Reconstitution System as a Support for Water Resources Management (Global Journals of Research in Engineering, 2012)
This paper presents a general system for the reconstitution of natural flows series to support the SNIRH Brazilian acronym for National Water Resources Information System There is a need for system structuring due to the fact that streamflows may suffer human modifications which difficult to carry out water resources management In order to make a reliable assessment it is essential to determine the socalled natural flow series i e the flows that would have occurred prior to human action The SisVazNat system was applied in the Tocantins watershed located in the Amazon Region and in order to validate the proposed methodology the results were compared with those published by the Electric System National Operator ONS The mean percent differences obtained in each hydropower plant were respectively UHE Serra da Mesa 3 2 UHE Cana Brava 5 6 UHE Lajeado 4 2 and UHE Tucuru 4 4 allowing the validation of the tool
Keywords: SisVazNat; water resources; natural flow reconstitution